Analisis dan Perbaikan Kerusakan Amplifier Merk Toa di PT Galva Technologies, Tbk - Sianturi, Niko Satria; Suraidi, Suraidi (VISA: Journal of Vision and Ideas, 2025)
The amplifier is a major component in an audio system that amplifies sound signals so they can be heard clearly through speakers. However, over time, amplifiers often experience damage caused by internal and external factors, such as component degradation, unstable electrical voltage, or short circuits. This study aims to analyze and repair damage to the TOA ZA-2120 amplifier, which is often used in public audio systems. The analysis process is carried out by examining the main components such as fuses, transistors, ICs, resistors, and PCB tracks using a multimeter. The repair method is carried out by replacing damaged components and retesting the amplifier's performance using a DC power supply and tools such as an oscilloscope and audio generator. The results of this activity show that through a systematic technical troubleshooting approach, the amplifier can be returned to normal working condition. This activity not only improves theoretical understanding but also trains students' practical skills in handling electronic equipment directly in an industrial environment.